Perlindungan Hukum oleh Pemerintah di Masa Pandemi Covid-19 - Wahyuni Wahyuni (Madika: Jurnal Politik dan Governance, 2021)
The importance of legal protection by the government during the current Covid-19 pandemic is increasingly felt by the community as an element affected either directly or indirectly. Based on data released by the Ministry of Health of the Republic of Indonesia regarding the soaring spread of Covid-19, the government is increasingly placed in the most responsible position for legal protection of the rights of its people. With unusual conditions like this, of course, the government needs to make extraordinary efforts in emergency transmission of Covid-19 by establishing forms of legislation and decisions. The government's authority in issuing policies is felt even more massive when the facts on the ground show a condition of rejection and indifference by the community. This condition has finally inspired the author to conduct a normative-empirical legal analysis using legal materials and field data and then conclude descriptively. Various efforts and legal steps have been taken by the government, both by the central government and local governments, to deal with the emergency of the Covid-19 outbreak, however, any legal protection efforts provided without the role and awareness of the community will not produce effective results. What we have to avoid is when the government takes firm steps by imposing sanctions for non-cooperatives, with efforts to increase legal awareness of the entire community on the dangers of this virus so that they actually take actions that are in line with efforts to contain Covid-19.